The Macroeconomic Imbalance Procedure: A useful tool for predicting sovereign crises? - Arahuetes García, Alejandro; Gómez Bengoechea, Gonzalo (Estudios de Economía, 2018)
This paper provides an empirical analysis of the Macroeconomic Imbalance Procedure (MIP). It explores the relationship between sovereign bond yields spreads and the variables contained in the MIP scoreboard using quantile regressions. Results suggest that MIP indicators can explain the behavior of sovereign spreads two, three and four quarters in advance. The scoreboard can’t capture strong non-variant country effects that affect the evolution of spreads as well as the different impact that each indicator has on different countries. The introduction of employment indicators has reduced the aggregate effect that country effects have on sovereign spreads.